A multi-rate ISM approach for robust vehicle stability control during cornering. Issue 9 (2018) - Regolin, E.; Zambelli, M.; Ferrara, A.
Abstract: In this paper a Model Predictive Control (MPC) architecture is proposed to achieve a smooth and progressive stabilization of the vehicle in limit cornering conditions. Integral Sliding Mode (ISM) is effectively exploited, in a multi-rate structure, in order to enhance the robustness with respect to changes in the tire/road friction characteristic curve and modelling errors. These typically arise due to the linearizations and discretizations needed in the controllers implementation. The performance is verified in simulation using IPG-CarMaker, a high-fidelity vehicle dynamics simulation software. The results obtained evidence the effectiveness of the proposed approach, also compared to an LQR based architecture.